A Technique for Absolute Haemostasis - A. L. Urakov (Креативная хирургия и онкология)
Background. Acute bleeding of parenchymal organs in blunt soft tissue traumas, sharp force injuries, bullet and shrapnel wounds is often lifethreatening due to hypoxia combined with haemorrhagic shock. Hypoxia and haemorrhagic shock develop due to a continuous blood outflow from multiple gaping noncontractile blood vessels. A safe and effective organpreserving surgery in parenchymal haemorrhage has not been developed to date.Materials and methods. A survey of scientific and patent literature has been conducted on techniques for parenchymal bleeding haemostasis based on topical cooling and heatingaided surgical interventions. Sources were mined in the Espacenet, Google Patent, eLibrary, Google Scholar, Web of Science, Scopus and PubMed databases.Results and discussion.An original method for parenchymal bleeding arrest was proposed in Russia at the end of the 20th century. The method is based on a safe transverse organ compression at vascular trunk to provide safe ischemia of the injured organ portion and using topical wound heating to trigger blood clotting. The compression is done with a surgical tool usually used for a gentle gastric or gut constriction. Mechanical  compression is applied at a force that ensures a complete constriction of the organ’s blood vessels arresting blood outflow from gaping vessels of the wound. Local hyperthermia of the wound surface is provided by a solid sterile object application with a smooth and slippery surface at +42–45 °C. Ischaemia and heating of the bleeding part of parenchymal organ are halted in 5–15 min. An adequacy criterion for the method is absolute haemostasis.Conclusion.An immediate arrest of blood supply to the wound surface complemented by heating at +42–45°С untill absolute haemostasis has been shown a sole rapid haemostatic technique effective in all forms of parenchymal haemorrhage. The entire peritoneal surface irrigation with 50% glycerol of pH 7.4 at +37–42 °С is advised to prevent postoperative abdominal adhesions at completion of surgery.